2003
DOI: 10.1063/1.1599049
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the thermoelectric properties of pressure-tuned β-K2Bi8Se13

Abstract: The thermoelectric power, electrical conductivity, crystal structure, and Raman active phonon modes of the semiconductor β-K2Bi8Se13 have been studied under pressure. There is a large increase in the electrical conductivity in the pressure range 0–1 GPa and a sharp maximum in the magnitude of the thermoelectric power at ∼1.4 GPa. X-ray diffraction studies revealed no structural change upon compression. The Raman active vibrational modes did not shift substantially with pressure, suggesting that the pressure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…To take into account the error introduced by the anvils, the sample was replaced by a piece of Pb with the value of thermopower close to zero (S = -1.27 µV/K) at room temperature [10]. Similar, but much more complicated techniques of thermoelectric measurements at high pressure P ≤ 12 GPa are developed now using natural diamond anvils [11].…”
Section: Methodsmentioning
confidence: 99%
“…To take into account the error introduced by the anvils, the sample was replaced by a piece of Pb with the value of thermopower close to zero (S = -1.27 µV/K) at room temperature [10]. Similar, but much more complicated techniques of thermoelectric measurements at high pressure P ≤ 12 GPa are developed now using natural diamond anvils [11].…”
Section: Methodsmentioning
confidence: 99%
“…11,12) Meng et al reported that the thermoelectric power and the electrical conduction for several materials were largely enhanced under high pressure. 13) Unfortunately, these properties could not be kept at room temperature after the pressure has been released. With the temperature tuning, these improved properties by pressure might be quenched at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…solid solutions [38,40], semiconductors [38,41], and high-temperature superconductors [42,43]. However, these materials need to be tuned to the LT by external pressure or doping.…”
mentioning
confidence: 99%